Econometrics for environmental policy evaluation : analysis of the ”priority municipalities” policy in the Brazilian Amazon - Gonçalves, Rodrigo Fernandes (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Economia, Administração e Contabilidade, Departamento de Economia, Programa de Pós-Graduação em Ciências Econômicas, 2022.